2020
DOI: 10.1016/j.brat.2019.103533
|View full text |Cite
|
Sign up to set email alerts
|

Peer supervision for assuring the quality of non-specialist provider delivered psychological intervention: Lessons from a trial for perinatal depression in Goa, India

Abstract: Background. The aims of the current study were three-fold: i) to estimate the reliability and predictive validity of a therapy quality measure for use by peers; ii) to assess the extent to which peer delivery agents could be trained to evaluate their peers' counsellors as reliably as experts; and iii) to identify barriers and facilitators of several implemented models of peer supervision. Methods. 26 peers (called 'Sakhis' in the study context), with no previous experience or formal training in mental health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Results from this study revealed that after piloting peer supervision, both drug sellers and peer supervisors felt that peer supervision was reliable, regular and predictable. These results are similar to those from India where peer supervisors were able to reliably assess the quality of a therapy just as experts did [24]. However, while an amalgamation of peer supervisors with experts was preferred in India, in Luuka District, peer supervisors preferred an amalgamation with drug inspectors for quality assurance purposes.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Results from this study revealed that after piloting peer supervision, both drug sellers and peer supervisors felt that peer supervision was reliable, regular and predictable. These results are similar to those from India where peer supervisors were able to reliably assess the quality of a therapy just as experts did [24]. However, while an amalgamation of peer supervisors with experts was preferred in India, in Luuka District, peer supervisors preferred an amalgamation with drug inspectors for quality assurance purposes.…”
Section: Discussionsupporting
confidence: 78%
“…Through repeated networking with fellow supervisees, peer supervision is seen as one of the best ways of accessing the wisdom of others in a cooperative and mutual way providing an opportunity to refine professional skills through immediate feedback [23]. Therefore, to strengthen supervision among drug sellers, it was envisaged that since peer supervision had been effective in other settings such as mental health care delivery [24], there was a likelihood that similar results would be achieved among drug sellers in rural settings in Uganda. The piloting of peer supervision among rural private drug sellers in Luuka District was premised on the fact that that despite being licensed, receiving iCCM training and being inspected by District Drug Inspectors (DDIs), inappropriate treatment of children under 5 years continues unabated [25].…”
mentioning
confidence: 99%
“…This study did not use therapy quality scales (TQS) to measure general and speci c skills of inspection and peer supervision during data collection [49]. Instead, views from participants were explored using a constructivist grounded theory approach by Kathy Charmaz [24].…”
Section: Study Limitationsmentioning
confidence: 99%
“…This study did not use therapy quality scales (TQS) to measure general and speci c skills of inspection and peer supervision during data collection [44]. Instead, views from participants were explored using a constructivist grounded theory approach by Kathy Charmaz [21].…”
Section: Study Limitationsmentioning
confidence: 99%